Composite precursor and preparation method thereof, positive electrode material and battery

The preparation of nano-sized metal oxide and hydroxide composite precursors by spray pyrolysis solves the problems of easy breakage and high cost of ternary positive electrode materials, realizes efficient battery material production, and improves the performance and industrialization potential of new energy vehicle batteries.

CN120717522APending Publication Date: 2025-09-30NANTONG JINTONG ENERGY STORAGE POWER NEW MATERIAL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510851089.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-24
Publication Date
2025-09-30

AI Technical Summary

Technical Problem

In the existing technology, the ternary positive electrode material is easy to break during the cycle, resulting in battery capacity decay, and the precursor preparation cost is high, which makes it difficult to meet the large-scale production needs of new energy vehicle batteries.

Method used

Nano-sized metal oxide and metal hydroxide composite precursors are prepared by spray pyrolysis. After mixing with additives, spray heat treatment is performed to form a composite precursor with a particle size of 5~50μm. After mixing with a lithium source, it is calcined at high temperature to form a single crystal lithium ion positive electrode material.

Benefits of technology

It significantly reduces the cost of precursor production, improves sintering activity and calcination loading, shortens calcination time, and improves the electrochemical performance and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120717522A_ABST
    Figure CN120717522A_ABST
Patent Text Reader

Abstract

The invention discloses a composite precursor and a preparation method thereof, a positive electrode material and a battery. Wherein the composite precursor is formed by compounding nanocrystallized metal oxide particles, metal hydroxides and additives, and has high sintering activity. In the sintering process, a full-area liquid phase environment formed by melting the additive can promote lithium ion diffusion, so that the sintering time is remarkably shortened; meanwhile, as the metal hydroxide has a layered structure similar to that of the target positive electrode material, the metal hydroxide can be used as a crystal nucleus to induce formation of the layered single-crystal positive electrode material, and the obtained single-crystal positive electrode material shows excellent electrochemical performance. In addition, the composite precursor is high in tap density, the calcining bowl loading amount is greatly increased, and the production cost is remarkably reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a composite precursor and a preparation method thereof, a positive electrode material and a battery. Background Art

[0002] Ternary cathode materials (LiNi x Co y Mn 1-x-y O2) has a very high specific capacity and is currently the mainstream positive electrode material in the electric passenger vehicle field. It is widely used in lithium-ion batteries for pure electric vehicles and plug-in hybrid vehicles. Currently, battery companies mostly use polycrystalline materials, but polycrystalline materials are prone to secondary particle breakage during the cycle process, resulting in rapid battery capacity degradation, affecting the range and service life of new energy vehicles. In contrast, single crystal materials can effectively suppress particle breakage and have better safety and cycle performance and higher compaction density. They are an important research and development direction for future ternary materials and are expected to further improve the energy density and cycle stability of new energy vehicle batteries.

[0003] The preparation of single-crystal ternary positive electrode materials is usually achieved by uniformly mixing lithium salts and precursor powders and high-temperature solid-phase calcination, and the process is relatively simple. However, industrially produced precursors are mostly prepared by co-precipitation, and their powder particle size is generally greater than 3μm, while the lithium salt particle size is usually 100~200μm. The raw material mixing scale is limited to the micron level, requiring a higher sintering temperature and a longer sintering time, which can easily cause lithium-nickel mixing, reduce the electrochemical performance of the positive electrode material, and thus affect the performance of the battery under the actual working conditions of new energy vehicles. If the precursor powder particle size is reduced, although the sintering activity can be improved and the electrochemical performance can be improved, the preparation of small-particle precursors is difficult, and there are problems such as low sintering capacity, insufficient production capacity, and high cost. It is difficult to meet the needs of the new energy vehicle industry for large-scale production of power batteries.

[0004] Nickel-cobalt-manganese oxide can be directly prepared by spray pyrolysis of a mixed solution of nickel, cobalt, and manganese chloride or nitrate salts. This method requires no precipitants or wastewater treatment, significantly reducing precursor manufacturing costs and promoting cost reduction and efficiency improvement in new energy vehicle batteries. However, nickel-cobalt-manganese oxide has low reactivity with lithium, requiring high sintering temperatures and long sintering times. It also needs to be crushed to approximately 1μm before use. It also faces challenges such as low loading capacity, insufficient production capacity, and high costs, which restrict its large-scale application in new energy vehicle power batteries.

[0005] In summary, how to significantly reduce the production cost of the precursor while improving its sintering activity, increasing the calcination load and controlling the cost is a key issue that technical personnel in this field urgently need to solve. The solution to these problems will directly affect the performance improvement and industrialization process of the next generation of new energy vehicle power batteries. Summary of the Invention

[0006] The purpose of the present invention is to provide a composite precursor and a preparation method thereof, a positive electrode material and a battery.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is: A composite precursor is a secondary particle formed by the accumulation of primary particles. The precursor is composed of metal oxides, metal hydroxides and additives. The particle size D50 is 5-50μm. The primary particles are nanosized and have a size of less than 500nm.

[0008] A further technical solution is that the chemical formula of the metal oxide is (Ni x1 Co y1 Mn z1 Al t1 ) a1 M1 b1 O c1 ; Among them, 0<x1<1, 0<y1<1, 0≤z1<1, 0≤t1<0.1, x1+y1+z1+t1=1, 0.9<a1≤1, 0≤b1<0.1, a1+b1=1, c1 satisfies the chemical valence balance; M1 is a combination of one or more of the elements calcium, magnesium, aluminum, titanium, zirconium, tungsten, yttrium, strontium, niobium, molybdenum, vanadium, tantalum, boron or phosphorus; The chemical formula of the metal hydroxide is (Ni x2 Co y2 Mn z2 Al t2 ) a2 M2 b2 (OH) c2 ; Among them, 0<x2<1, 0<y2<1, 0≤z2<1, 0≤t2<0.1, x2+y2+z2+t2=1, 0.9<a2≤1, 0≤b2<0.1, a2+b2=1, c2 satisfies the chemical valence balance; M2 is a combination of one or more of the elements calcium, magnesium, aluminum, titanium, zirconium, tungsten, yttrium, strontium, niobium, molybdenum, vanadium, tantalum, boron or phosphorus; The additive is a combination of one or more carbonates, oxides, and hydroxides of element M3, where M3 is a combination of one or more elements of calcium, magnesium, aluminum, titanium, zirconium, tungsten, yttrium, strontium, niobium, molybdenum, vanadium, tantalum, boron, or phosphorus.

[0009] According to a further technical solution, the proportion of the metal oxide in the total mass of the metal oxide and the metal hydroxide is 0-1, and the ratio of the additive to the total mass of the metal oxide and the metal hydroxide is 0-0.1.

[0010] Furthermore, the present invention also discloses a method for preparing a composite precursor, comprising: S1. Preparation of Metal Oxides Dissolving and mixing a first nickel salt, a first cobalt salt, a first manganese salt and / or a first aluminum salt, and an M1 salt to obtain a first metal liquid with a metal concentration of 0.5 to 5.0 mol / L; spray pyrolysis of the first metal liquid to obtain a metal oxide; S2. Preparation of Metal Hydroxides Mixing and dissolving a second nickel salt, a second cobalt salt, a second manganese salt and / or a second aluminum salt to obtain a second metal liquid having a metal concentration of 1.0 to 2.5 mol / L; dissolving the M2 salt to obtain an M2 salt solution; Adding pure water, complexing agent and precipitant into the reaction kettle as reaction bottom liquid; The second metal liquid, the complexing agent, the precipitant and the M2 salt solution are continuously added to the reactor simultaneously, and the temperature, complexing agent concentration and solution pH in the reactor are maintained to perform a coprecipitation reaction; After the reaction stops, the product is filtered, washed, and dried to obtain a metal hydroxide; S3. Crushing the metal oxide and the metal hydroxide, adding them to pure water with additives and grinding them into nanoparticles with D50 less than 1 μm, and then spray heat treatment to obtain the composite precursor.

[0011] In a further technical solution, in S1, the first nickel salt is a combination of one or more of nickel nitrate, nickel chloride, and nickel acetate; The first cobalt salt is a combination of one or more of cobalt nitrate, cobalt chloride, and cobalt acetate; The first manganese salt is a combination of one or more of manganese nitrate, manganese chloride, and manganese acetate; The first aluminum salt is a combination of one or more of aluminum nitrate, aluminum chloride, and aluminum acetate; The M1 salt is a combination of one or more of calcium salt, magnesium salt, titanium salt, zirconium salt, tungsten salt, yttrium salt, strontium salt, niobium salt, molybdenum salt, vanadium salt, tantalum salt, borate or phosphate; In S2, the second nickel salt is a combination of one or more of nickel sulfate, nickel chloride, nickel nitrate, and nickel acetate; The second cobalt salt is a combination of one or more of cobalt sulfate, cobalt chloride, cobalt nitrate, and cobalt acetate; The second manganese salt is a combination of one or more of manganese sulfate, manganese chloride, manganese nitrate, and manganese acetate; The second aluminum salt is a combination of one or more of aluminum sulfate, aluminum chloride, aluminum nitrate, and aluminum acetate; The M2 salt is a combination of one or more of calcium salts, magnesium salts, aluminum salts, titanium salts, zirconium salts, borates, tungsten salts, yttrium salts, strontium salts, niobium salts, molybdenum salts, vanadium salts, tantalum salts, borates or phosphates; The complexing agent is a combination of one or more of ammonia water, ammonium sulfate, ammonium chloride, ammonium carbonate, ammonium bicarbonate, ammonium nitrate, and ammonium acetate; The precipitant is a combination of one or more of sodium hydroxide and potassium hydroxide.

[0012] In a further technical solution, the additive is a combination of one or more carbonates, oxides, hydroxides of element M3, and M3 is a combination of one or more elements of calcium, magnesium, aluminum, titanium, zirconium, tungsten, yttrium, strontium, niobium, molybdenum, vanadium, tantalum, boron or phosphorus.

[0013] In a further technical solution, in S1, the atomization method of the spray pyrolysis is one of pressure spray, centrifugal spray, and ultrasonic spray, the droplet size is less than 100 μm, and the pyrolysis temperature is 600-1200°C; In S2, the reaction temperature is 40-75°C, the complexing agent concentration is 0.2-0.5 mol / L, and the pH range is 10.60-12.60; In S3, the atomization method of spray pyrolysis is one of pressure spray, centrifugal spray, and ultrasonic spray, the droplet size is less than 100 μm, and the pyrolysis temperature is 150~900℃.

[0014] Furthermore, the present invention also discloses a lithium-ion battery positive electrode material, which is obtained by mixing the composite precursor with a lithium source, calcining it under high temperature and oxygen atmosphere, and crushing it to obtain a single crystal lithium-ion positive electrode material with a chemical formula of Li(Ni x Co y Mn z Al t ) a M b O c , where 0<x<1, 0<y<1, 0≤z<1, 0≤t<0.1, x+y+z+t=1, 0.9<a≤1, 0≤b<0.1, a+b=1, c satisfies the chemical valence balance; M is one or more of the elements calcium, magnesium, aluminum, titanium, zirconium, tungsten, yttrium, strontium, niobium, molybdenum, vanadium, tantalum, boron or phosphorus; The particle size D50 of the positive electrode material is 3~5μm.

[0015] In a further technical solution, the lithium source is a combination of one or more of lithium carbonate, lithium bicarbonate, and lithium hydroxide; the calcination temperature is 650°C to 1100°C, the oxygen concentration of the oxygen atmosphere is 60% to 100%, and the calcination time is 8 to 12 hours.

[0016] Furthermore, the present invention also discloses a lithium-ion battery, comprising a positive electrode plate, wherein the positive electrode plate is made of the lithium-ion battery positive electrode material.

[0017] The terms “include”, “including”, “have”, etc. used in this document are open-ended terms, meaning including but not limited to.

[0018] Unless otherwise noted, the terms used herein generally have their ordinary meanings in the art, in the context of this application, and in the specific context. Certain terms used to describe this application are discussed below or elsewhere in this specification to provide additional guidance to those skilled in the art regarding the description of this application.

[0019] The working principle and advantages of the present invention are as follows: Compared to existing technologies, this invention nanosizes low-cost metal oxides (spray pyrolysis products), metal hydroxides (coprecipitation products), and additives, then spray pyrolysis to produce a composite precursor. The nanosized metal oxides and metal hydroxides exhibit excellent sintering reactivity, while the additives melt at low temperatures, placing the metal oxides and metal hydroxides in a liquid phase, promoting lithium ion diffusion and lowering the sintering temperature. Furthermore, the metal hydroxides, with a layered structure similar to that of the target cathode material, act as crystal nuclei to induce the formation of layered single-crystalline cathode materials, ultimately yielding single-crystalline cathode materials with excellent electrochemical performance. This composite precursor exhibits a large particle size, high calcination yield, and significantly reduced production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Attachment Figure 1 This is an electron microscope image of the composite precursor prepared in Example 1 of the present invention; Attachment Figure 2 This is an electron microscope image of the single crystal positive electrode material prepared in Example 1 of the present invention; Attachment Figure 3 This is an electron microscope image of the metal hydroxide prepared in Comparative Example 1 of the present invention; Attachment Figure 4 This is an electron microscope image of the metal oxide prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0021] The present invention will be further described below with reference to the accompanying drawings and embodiments: The present invention will be clearly illustrated below with drawings and detailed descriptions. After understanding the embodiments of the present invention, any person skilled in the art will be able to make changes and modifications based on the techniques taught by the present invention without departing from the spirit and scope of the present invention.

[0022] The terms used herein are for describing specific embodiments only and are not intended to be limiting of the present invention. Singular forms such as "a," "the," "this," "this," and "the" as used herein also include plural forms.

[0023] Example 1: comprising the following steps: S1. Preparation of Metal Oxides a. Prepare a 2.0 mol / L first metal liquid by mixing nickel chloride, cobalt chloride, manganese chloride and magnesium chloride, wherein the ratio of nickel, cobalt and manganese is 65:15:20, and the ratio of the total amount of nickel, cobalt and manganese to magnesium is 99:1; magnesium chloride is used as the M1 salt.

[0024] b. The first metal liquid is subjected to centrifugal spray pyrolysis with a droplet size of 50 μm and a pyrolysis temperature of 800°C to obtain a metal oxide with the chemical formula (Ni 0.65 Co 0.15 Mn 0.20 ) 0.99 Mg 0.01 O 2.4 , particle size D50 = 10 μm, primary particles 200 ~ 300 nm; S2. Preparation of Metal Hydroxides Nickel chloride, cobalt chloride and manganese chloride are prepared into a 2.0 mol / L second metal solution at a molar ratio of nickel, cobalt and manganese of 65:15:20; magnesium chloride is dissolved to obtain a 1.0 mol / L salt solution.

[0025] b. Add pure water, ammonia water and 32% concentration of NaOH into the reactor as the reaction base liquid; c. The second metal liquid, ammonia water, magnesium chloride solution, and 32% NaOH were continuously added to the reactor, and the temperature in the reactor was maintained at 50°C, the ammonia concentration was 0.1 mol / L, and the pH was 11.5, to carry out a coprecipitation reaction; d. After the reaction stops, the product is filtered, washed, and dried to obtain a metal hydroxide, the chemical formula of which is (Ni 0.65 Co 0.15 Mn 0.20 ) 0.99 Mg 0.01 O 2.4 , particle size D50 = 3.8 μm; S3, adding the metal oxide, the metal hydroxide and the M3 additive boric acid into pure water for grinding, wherein the metal oxide accounts for 0.9 of the total mass of the metal oxide and the metal hydroxide, and the ratio of the additive boric acid to the total mass of the metal oxide and the metal hydroxide is 0.005. After grinding until the particles are nanoparticles (D50=0.5μm), spray heat treatment is performed, with a droplet size of 60μm and a heat treatment temperature of 200°C to obtain a lithium ion composite precursor with D50=10.3μm; S4, mixing the composite precursor with lithium carbonate, wherein Li:(Ni+Co+Mn)=1.06, sintering at 900℃ in oxygen atmosphere for 12 hours, and then crushing to obtain a single crystal lithium ion battery positive electrode material, the chemical formula is Li(Ni 0.65 Co 0.15 Mn 0.20 ) 0.99 Mg 0.01 O2, particle size D50=4.2μm.

[0026] Comparative Example 1: comprising the following steps: S1. Prepare a 2.0 mol / L second metal liquid by mixing nickel chloride, cobalt chloride, manganese chloride, and magnesium chloride, wherein the molar ratio of nickel to cobalt to manganese is 65:15:20, and the molar ratio of the total number of moles of nickel, cobalt, and manganese to the molar number of magnesium is 99:1; S2, adding pure water, complexing agent and precipitant into the reactor as reaction bottom liquid; S3, continuously adding the second metal liquid, ammonia water, and 32% concentration of NaOH into the reactor, maintaining the temperature in the reactor at 50°C, the ammonia concentration at 0.1 mol / L, and the pH at 11.5, to carry out a coprecipitation reaction; S4. After the reaction stops, the product is filtered, washed, and dried to obtain a metal hydroxide. The chemical formula is (Ni 0.65 Co 0.15 Mn 0.20 ) 0.99 Mg 0.01 (OH)2, particle size D50 = 3.8 μm; S5. Mix metal hydroxide, lithium carbonate, and additive boric acid, wherein Li:(Ni+Co+Mn)=1.06 and the mass ratio of boric acid to metal hydroxide is 0.005; after mixing, sinter at 950°C in an oxygen atmosphere for 20 hours, and then crush to obtain a single crystal lithium ion battery positive electrode material, the chemical formula of which is Li(Ni 0.65 Co 0.15 Mn 0.20 ) 0.99 Mg 0.01 O2, particle size D50 is 4.2μm.

[0027] Comparative Example 2: comprising the following steps: S1, nickel chloride, cobalt chloride, and manganese chloride are prepared into a 2.0 mol / L metal solution at a molar ratio of nickel, cobalt, and manganese of 65:15:20; S2, spray pyrolysis of the metal liquid, with a droplet size of 50 μm and a pyrolysis temperature of 800 ° C, to obtain metal oxides with the chemical formula Ni 0.65 Co 0.15 Mn 0.20 O2.4 , particle size D50 = 10 μm, primary particles 200 ~ 300 nm; S3, crushing the metal oxide to obtain small particles of metal oxide, D50 = 1.5 μm; S3, small particles of metal oxide, lithium carbonate, and additive boric acid are mixed, Li: (Ni + Co + Mn) = 1.04, the mass ratio of boric acid to small particles of metal oxide is 0.005, and then sintered at 920 ° C in an oxygen atmosphere for 20 hours, and crushed to obtain a single crystal lithium ion battery positive electrode material, the chemical formula is LiNi 0.65 Co 0.15 Mn 0.2 O2, particle size D50 is 4.2μm.

[0028] Table 1 Electrical properties of single crystal cathode materials

[0029] From the above Table 1, it can be seen that ( Figures 1 to 4 ), Example 1 of the present invention has a large composite precursor particle size and a high tap density, so the filling amount is large, the metal oxide and metal hydroxide therein are all nanoparticles, and the metal hydroxide serves as the crystal nucleus, so the single crystal after sintering is more rounded and has better electrochemical properties after sintering. However, since the precursor of Comparative Example 1 is small-particle hydroxide particles, the electrochemical performance after sintering is close to that of Example 1, but the filling amount is small and the sintering time is long; the precursor of Comparative Example 2 is a crushed metal oxide with low activity and poor electrochemical properties after sintering. At the same time, the precursor particles are small, resulting in a small filling amount and low production capacity.

[0030] In summary, the present invention directly prepares a highly active composite precursor by spray pyrolysis of low-cost nano-metal oxide particles, metal hydroxides, and additives, resulting in a high calcination capacity and low production costs. During the calcination process, the liquid phase formed by the melting of the additives promotes lithium ion diffusion, thereby shortening the calcination time. Furthermore, the metal hydroxide, with a layered structure similar to that of the target cathode material, acts as a crystal nucleus to induce the formation of a layered single-crystal cathode material, ultimately resulting in a material with superior electrochemical performance.

[0031] The above embodiments are intended only to illustrate the technical concepts and features of the present invention. Their purpose is to enable those skilled in the art to understand the contents of the present invention and implement them accordingly. They are not intended to limit the scope of protection of the present invention. Any equivalent changes or modifications made in accordance with the spirit of the present invention are intended to be covered by the scope of protection of the present invention.

Claims

1. A composite precursor, characterized in that: The precursor is a secondary particle formed by the accumulation of primary particles, which is composed of a composite of metal oxides, metal hydroxides and additives. The particle size D50 is 5~50μm, and the primary particles are nano-sized and less than 500nm in size.

2. A composite precursor according to claim 1, characterized in that: The chemical formula of the metal oxide is (Ni x1 Co y1 Mn z1 Al t1 ) a1 M1 b1 O c1 ; Among them, 0<x1<1, 0<y1<1, 0≤z1<1, 0≤t1<0.1, x1+y1+z1+t1=1, 0.9<a1≤1, 0≤b1<0.1, a1+b1=1, c1 satisfies the chemical valence balance; M1 is a combination of one or more of the elements calcium, magnesium, aluminum, titanium, zirconium, tungsten, yttrium, strontium, niobium, molybdenum, vanadium, tantalum, boron or phosphorus; The chemical formula of the metal hydroxide is (Ni x2 Co y2 Mn z2 Al t2 ) a2 M2 b2 (OH) c2 ; Among them, 0<x2<1, 0<y2<1, 0≤z2<1, 0≤t2<0.1, x2+y2+z2+t2=1, 0.9<a2≤1, 0≤b2<0.1, a2+b2=1, c2 satisfies the chemical valence balance; M2 is a combination of one or more of the elements calcium, magnesium, aluminum, titanium, zirconium, tungsten, yttrium, strontium, niobium, molybdenum, vanadium, tantalum, boron or phosphorus; The additive is a combination of one or more carbonates, oxides, and hydroxides of element M3, where M3 is a combination of one or more elements of calcium, magnesium, aluminum, titanium, zirconium, tungsten, yttrium, strontium, niobium, molybdenum, vanadium, tantalum, boron, or phosphorus.

3. The composite precursor according to claim 1, characterized in that: The proportion of metal oxide in the total mass of metal oxide and metal hydroxide is 0-1, and the ratio of additive to the total mass of metal oxide and metal hydroxide is 0-0.

1.

4. A method for preparing a composite precursor, characterized in that: A composite precursor for preparing any one of claims 1 to 3, the preparation method comprising: S1. Preparation of Metal Oxides Dissolving and mixing a first nickel salt, a first cobalt salt, a first manganese salt and / or a first aluminum salt, and an M1 salt to obtain a first metal liquid with a metal concentration of 0.5 to 5.0 mol / L; spray pyrolysis of the first metal liquid to obtain a metal oxide; S2. Preparation of Metal Hydroxides Mixing and dissolving a second nickel salt, a second cobalt salt, a second manganese salt and / or a second aluminum salt to obtain a second metal liquid having a metal concentration of 1.0 to 2.5 mol / L; dissolving the M2 salt to obtain an M2 salt solution; Adding pure water, complexing agent and precipitant into the reaction kettle as reaction bottom liquid; The second metal liquid, the complexing agent, the precipitant and the M2 salt solution are continuously added to the reactor simultaneously, and the temperature, complexing agent concentration and solution pH in the reactor are maintained to perform a coprecipitation reaction; After the reaction stops, the product is filtered, washed, and dried to obtain a metal hydroxide; S3. Crushing the metal oxide and the metal hydroxide, adding them to pure water with additives and grinding them into nanoparticles with D50 less than 1 μm, and then spray heat treatment to obtain the composite precursor.

5. The method for preparing a composite precursor according to claim 4, characterized in that: In S1, the first nickel salt is a combination of one or more of nickel nitrate, nickel chloride, and nickel acetate; The first cobalt salt is a combination of one or more of cobalt nitrate, cobalt chloride, and cobalt acetate; The first manganese salt is a combination of one or more of manganese nitrate, manganese chloride, and manganese acetate; The first aluminum salt is a combination of one or more of aluminum nitrate, aluminum chloride, and aluminum acetate; The M1 salt is a combination of one or more of calcium salt, magnesium salt, titanium salt, zirconium salt, tungsten salt, yttrium salt, strontium salt, niobium salt, molybdenum salt, vanadium salt, tantalum salt, borate or phosphate; In S2, the second nickel salt is a combination of one or more of nickel sulfate, nickel chloride, nickel nitrate, and nickel acetate; The second cobalt salt is a combination of one or more of cobalt sulfate, cobalt chloride, cobalt nitrate, and cobalt acetate; The second manganese salt is a combination of one or more of manganese sulfate, manganese chloride, manganese nitrate, and manganese acetate; The second aluminum salt is a combination of one or more of aluminum sulfate, aluminum chloride, aluminum nitrate, and aluminum acetate; The M2 salt is a combination of one or more of calcium salts, magnesium salts, aluminum salts, titanium salts, zirconium salts, borates, tungsten salts, yttrium salts, strontium salts, niobium salts, molybdenum salts, vanadium salts, tantalum salts, borates or phosphates; The complexing agent is a combination of one or more of ammonia water, ammonium sulfate, ammonium chloride, ammonium carbonate, ammonium bicarbonate, ammonium nitrate, and ammonium acetate; The precipitant is a combination of one or more of sodium hydroxide and potassium hydroxide.

6. The method for preparing a composite precursor according to claim 4, characterized in that: The additive is a combination of one or more carbonates, oxides, and hydroxides of element M3, where M3 is a combination of one or more elements of calcium, magnesium, aluminum, titanium, zirconium, tungsten, yttrium, strontium, niobium, molybdenum, vanadium, tantalum, boron, or phosphorus.

7. The method for preparing a composite precursor according to claim 4, characterized in that: In S1, the atomization method of spray pyrolysis is one of pressure spray, centrifugal spray, and ultrasonic spray, the droplet size is less than 100 μm, and the pyrolysis temperature is 600~1200℃; In S2, the reaction temperature is 40-75°C, the complexing agent concentration is 0.2-0.5 mol / L, and the pH range is 10.60-12.60; In S3, the atomization method of spray pyrolysis is one of pressure spray, centrifugal spray, and ultrasonic spray, the droplet size is less than 100 μm, and the pyrolysis temperature is 150~900℃.

8. A lithium-ion battery cathode material, characterized in that: A single crystal lithium ion positive electrode material is obtained by mixing a composite precursor according to any one of claims 1 to 3 with a lithium source, calcining the mixture under high temperature and oxygen atmosphere, and crushing the mixture to obtain a single crystal lithium ion positive electrode material with a chemical formula of Li(Ni x Co y Mn z Al t ) a M b O c , where 0<x<1, 0<y<1, 0≤z<1, 0≤t<0.1, x+y+z+t=1, 0.9<a≤1, 0≤b<0.1, a+b=1, c satisfies the chemical valence balance; M is one or more of the elements calcium, magnesium, aluminum, titanium, zirconium, tungsten, yttrium, strontium, niobium, molybdenum, vanadium, tantalum, boron or phosphorus; The particle size D50 of the positive electrode material is 3~5μm.

9. A lithium-ion battery positive electrode material according to claim 8, characterized in that: The lithium source is a combination of one or more of lithium carbonate, lithium bicarbonate, and lithium hydroxide; The calcination temperature is 650° C. to 1100° C., the oxygen concentration of the oxygen atmosphere is 60% to 100%, and the calcination time is 8 to 16 hours.

10. A lithium-ion battery, characterized in that: The invention comprises a positive electrode plate, wherein the positive electrode plate is made of a lithium-ion battery positive electrode material according to any one of claims 8 or 9.

Citation Information

Patent Citations

  • Preparation method of layered lithium-rich manganese base oxide of positive material of lithium ion battery

    CN102683645A

  • Ternary cathode material, precursor thereof, and preparation method of ternary cathode material and precursor

    CN107585794A

  • Composite in-situ coated high-nickel single-crystal positive electrode material and preparation method thereof

    CN115571927A

  • Composite multi-element precursor as well as preparation method and application thereof

    CN116002774A

  • Single-crystal positive electrode material, preparation method thereof and lithium ion battery

    CN116487580A